The Effect of Interpersonal Communication and Work Satisfaction on Teacher Performance at SD Negeri Bandar Baru, Pidie Jaya Aceh - Darmawati Darmawati; Zainuddin Zainuddin; Benyamin Situmorang; Nasrun Nasrun; Akmaluddin Akmaluddin (Budapest International Research and Critics University, 2020)
The purpose of this study is to determine and review: (1) teacher performance models that are built based on the associative causal relationship between exogenous variables and endogenous variables, (2) the effect of interpersonal communication on job satisfaction, (3) the effect of interpersonal communication on teacher performance, (4) the effect of satisfaction on teacher performance. This research was conducted in elementary schools with 154 respondents from 28 public elementary schools in Pidie Jaya. For questionnaire data collection with five alternative answer choices, while for the performance variable is done by observation using an observation sheet. The sampling technique used is proportional random sampling. The instrument used was preceded by a trial to respondents outside the sample to obtain a valid and relative instrument. Validity test uses product moment correlation, whereas to test its reliability with the Alpha formula from Cronbach. Before testing the hypothesis first, the analysis requirements test is calculated including the data normality test and the regression linearity test. The results showed (1) obtained by the teacher performance model, (2) Interpersonal communication had a direct positive effect on job satisfaction, (3) Interpersonal communication had a direct positive effect on teacher performance, (4)Job satisfaction had a positive direct effect on teacher performance. Based on the acceptance of research hypotheses, a theoretical model or fixed model is found that describes the structure of the causal relationship between Interpersonal Communication variables, organizational culture, job satisfaction, work motivation and teacher performance while to test its reliability with the Alpha formula from Cronbach.